Pemenuhan Hak Ekosob Dibidang Pekerjaan, Pangan Dan Perumahan Bagi Masyarakat Miskin Kelurahan Pucangsawit Kota Surakarta - Bhakti, Dyana Lifiani Patriana; , Jaka Susila, S.H., M.Si., M.H; , Iswanto, S.H., M.H (2016)
This research will exemine the regulations and the realization of the fulfillment of economic, social and cultural rights in the field of right to work, food and housing to the poor people in Kelurahan Pucang Sawit, Surakarta. This research uses empirical juridical approach. The result shows that Surakarta City Government has taken legislative steps to establish regional regulations relating to fulfillment of the right to work, food and housing, namely Local Regulation of Surakarta Number 11 Year 2014 on Poverty Reduction and Regulatory Mayor of Surakarta No. 2-H in 2013 on a Strategy Regional Poverty Reduction (PRSP) Surakarta in accordance with Article 2 Verse (1) of the International Covenant on Economic, Social and Cultural Rights. Surakarta City Government has made efforts to fulfill the right to work, food and housing for the poor people, especially in Kelurahan Pucang Sawit, but the fulfillment of these rights have not been fully realized, as stated in the International Covenant on Economic, Social and Cultural Rights. Keywords: Rights fulfillment, Economic, social and cultural rights, Poor People